PENGARUH CAHAYA TERHADAP TINGKAT KELANGSUNGAN HIDUP DAN PERTUMBUHAN KARANG LUNAK LOBOPHYTUM STRICTUM (OCTOCORALIA: ALCYONACEA) HASIL TRANSPLANTASI PADA SISTEM RESIRKULASI - Beginer Subhan; Dedi Soedharma; Dondy Arafat; Hawis Madduppa; Fadillah Rahmawati; Ayu Ervinia; Aditya Bramandito; Denny Khaerudi; Ahmad Taufik Ghozali (Fakultas Perikanan dan Ilmu Kelautan, 2012)
The current research was conducted to investigate the effect of light on growth of soft coral Lobophytum strictum. This species was transplanted and reared in two different ponds, uncovered pond (with light penetration) and covered pond (no light penetration. A total of 16 coral fragments was placed on each pond. Both, the survival rate and the growth rate were significantly different on the effect of light (P<0.05). The soft coral on the uncovered pond was survive up to 12 weeks (100%), followed with increased length (from 5,95 to 10,04 cm) and width (from 5,27 to 6,84 cm) of the transplanted coral fragments. Conversely, the soft coral in the covered ponds showed survival rate of 62,5% (up to 8th week), with decreased length (from 8,25 to 5,25 cm) and width (from 9,14 to 4,86 cm) of each fragments during the period of study.